The role of the principal's instructional leadership at schools in Indonesia - Firmaningsih-Kolu, Yunita (2016)
The education system in Indonesia, based on Ministry of National Education, has been performing instructional leadership as a major part of the effective school leaders’ behavior. One of the goals of instructional leadership implementation is to increase the learning outcomes of students. However, many of international student assessments have shown that Indonesia’s education system was among the incompetent countries. The purpose of the study is to analyze the implementation of instructional leadership phenomenon as the basic concept of effective leadership.